The underlying states of salesperson product buy-in and product strategy buy-in. Issue 6 (16th November 2020) - Zeiss, Jessica; Chapman, Joseph
Abstract : Purpose: The purpose of this study is to collect data that allows researchers to capture both affective and cognitive buy-in influenced by both product and product strategy targets. Design/methodology/approach: Analysis of 13 salesperson interviews followed the cluster and axial coding of grounded theory interview protocol. Findings: This study finds two types of buy-in that are uniquely contingent on the target, and for which are influenced by both cognitive and affective states of being. Additionally, it finds that either affective or cognitive states of being can both drive and inhibit salesperson buy-in of either target. While the targets of buy-in appear to be mutually exclusive, the cognitive nature of disconfirming evidence appears to directly inhibit both targets of buy-in while also resulting in negative affect. Research limitations/implications: Further study that uncovers the causal role of an affective state inhibiting buy-in after the introduction of disconfirming evidence is warranted. Practical implications: Managerial training and messaging approaches for achieving the two buy-in targets will likely differ or focus on only one type for efficient training. Originality/value: This study is the first to examine the simultaneous effects of the two underlying states of cognition and affect on buy-in development. It is found that the two states can influence each other to stunt buy-in. The present study contributes to sales behavior literature by allowing the possibility of a sequence of states that stunt buy-in, positioning simultaneous examination is vital to the conceptualization of buy-in.